Beals–Hecht syndrome and choroidal neovascularization - Roberto Gallego-Pinazo (Dove Medical Press, 2010)
Roberto Gallego-Pinazo1, Ruth López-Lizcano1, José María Millán2,3, J Fernando Arevalo5, J Luis Mullor6, Manuel Díaz-Llopis1,3,41Department of Ophthalmology, 2Department of Genetics, Unit of Experimental Opthalmology, Hospital Universitario La Fe, Valencia, Spain; 3Centro de Investigación Biomédica en Red de Enfermedades Raras (CIBERER), Valencia, Spain; 4Faculty of Medicine, University of Valencia, Valencia, Spain; 5Retina and Vitreous Service, Clínica Oftalmológica Centro Caracas, Caracas, Venezuela; 6Unit of Experimental Opthalmology, Fundación Parala Investigación del Hospital La Fe, Valencia, SpainPurpose: To describe a case of choroidal neovascularization (CNV) in a female diagnosed with Beals–Hecht syndrome.Methods: A retrospective, interventional case is described in a 26-year-old female complaining of metamorphopsia and visual loss in her left eye (counting fingers). The fluorescein angiogram and the optical coherence tomography supported the diagnosis of CNV. Intravitreal ranibizumab was administered.Results: After the third intravitreal ranibizumab, her visual acuity improved to 0.8 and the morphology of the macular area was restored.Conclusions: To our knowledge this is the first report of CNV in Beals–Hecht syndrome treated with ranibizumab. Self-monitoring by periodically performing Amsler grid test is strongly recommended in these patients in order to achieve an early diagnosis of eventual CNV and avoid visual acuity loss.Keywords: Beals–Hecht syndrome, connective tissue disease, choroidal neovascularization, ranibizumab